The application of flow cytometry and a thioredoxin‐like nuclear gene for breeding Poa arachnifera x Poa pratensis hybrids. Issue 5 (1st September 2015) - Meeks, Meghyn; Chandra, Ambika; Staub, J.
Abstract Interspecific hybridization between Poa arachnifera Torr. (Texas bluegrass) and Poa pratensis L. (Kentucky bluegrass) has shown to be a proven method for the development of turf‐type hybrid bluegrass cultivars for the southern United States. Unlike in P. pratensis, the use of DNA markers for molecular characterization and flow cytometry to determine nuclear DNA contents has not been extensively utilized in P. arachnifera. In this study, 2C nuclear DNA content of 19 different genotypes of P. arachnifera (both males and females) was determined to range from 8.02 to 13.24 pg/2C using flow cytometry. The DNA content of the hybrids between P. arachnifera and P. pratensis from two different pedigrees was found to be intermediate between their parents. Furthermore, the utility of the trx (thioredoxin‐like) nuclear gene in the identification of interspecific hybrids between P. arachnifera and P. pratensis was demonstrated using sequence and phylogenetic analyses. A newly discovered 851‐bp trx allele may serve as a useful marker to differentiate P. arachnifera from P. pratensis and provide insights into the evolutionary origin of P. arachnifera.